How to evaluate nature-based solutions performance for microclimate, water and soil management issues – Available tools and methods from Nature4Cities European project results. (June 2021) - Bouzouidja, Ryad; Cannavo, Patrice; Bodénan, Philippe; Gulyás, Ágnes; Kiss, Márton; Kovács, Attila; Béchet, Béatrice; Chancibault, Katia; Chantoiseau, Etienne; Bournet, Pierre-Emmanuel; Bouzidi, Rania; Guénon, René; et al.
Highlights: An evaluation toolbox to consider nature-based solutions in urban areas is settled. Impact of nature-based solutions depends on urban environmental challenges. A decision-support methodology considering soil-water-climate aspects is developed. Several indicators were determined and compared to define the toolbox. Abstract: In the context of climate change, Nature-Based Solutions (NBSs), a recently developed concept, are increasingly considered as part of the adaptation strategies of the cities. Studies using expert models and methods (EMM) receive a great deal of scientific attention. Considering EMM increasing use, this study aims to perform an analysis of the reported evaluation results, reflecting the capability of the EMM to accurately tackle urban challenges identified within the EU Nature4Cities project. Then, we propose a set of indicators and recommendations about sixteen EMM to be used by funders, researchers and practitioners when evaluating the performance of NBSs. The coupling of the different components (climate, water and soil) is not a simple matter. The analysis relies on the definition of the range of the reported metrics and on the investigation of the relationship between the various indices, applied for the EMM evaluation. Secondly, the study assesses the existing EMM, indicating the potential of NBSs: (i) to reduce urban heat island, (ii) to limit surface warming, (iii) to increase the thermal comfort of people, (iv) to limit the overheating and runoff of surfaces due to impervious areas, (v) to increase water retention during stormy episodes, (vi) to improve storm water quality at the outlet of the sustainable urban drainage systems, (vii) to promote the filtration and epuration of storm water runoff in soil and (viii) to be a support for vegetation. The analysis reveals that EMM can be considered as helpful tools for urban microclimate, urban soil and water management analysis, provided their limitations and characteristics are taken into account by the user when choosing tools and interpreting results (e.g. application scale). With regard to the performance of NBSs, the most commonly used indicators clearly depend on the scale of the project.